Assessment on Knowledge, Attitude and, Behavior of Myanmar Instructors in the Context of Education 5.0 Principles - Atar Thaung Htet (Education Policy and Development, 2025)
As education evolves alongside technological advancements, it is crucial to understand how instructors perceive and adopt modern teaching methodologies, including artificial intelligence (AI), project-based learning, cooperative learning, gamification, and learning management systems (LMS). The primary aim of this study is to examine the knowledge, attitudes, and behaviors of Myanmar instructors in the context of Education 5.0 principles. The study employs a survey method, involving 102 instructors employed in private higher education institutions. Findings indicate a strong correlation between knowledge, attitude, and behavior, suggesting familiarity with the principles of Education 5.0. Furthermore, the study highlights a gap in scale development concerning these education 5.0 principles, positioning this research as a step toward filling this void. The implications of these findings are significant for private higher education institutions in Myanmar, offering valuable insights into curriculum development, instructor training, and the integration of technology in education.